The Value Perception in Luxury Goods Towards Purchase Intention Moderated By Disposable Income - Ariyanti, Maya; Rinarika, Dewi (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
Purpose – This paper seeks to introduce a fresh dimension to the concept of luxury perception, drawing from a synthesis of previous research frameworks. Consequently, the study underscores the importance of assessing the reliability and validity of variables within a culturally diverse environment, particularly within Indonesia's context. The chance of a business opportunity based on changes in the dynamics of the bicycle market that has occurred since the COVID-19 outbreak is the reason for researchers to investigate consumer buying interest, especially purchasing bicycles.. Methodology/approach – A survey that included information on Luxury Value Perception towards purchase intention that moderated by Disposable income was used to collect data from 414 respondents, whom since the Pandemic outbreak searching and seeking info about buying a bicycle. Findings – It was found that hedonic value, social value, and uniqueness value towards purchase intention were generally significant predictors while the other value have weak significancy, and the disposable income in general were positively and significantly influence the purchase intention.